Data must underpin our response to the covid-19 pandemic's disastrous impact on cancer. (2nd February 2022) - Lawler, Mark; Crul, Mirjam
Abstract : Unless we take action, the current pandemic will precipitate a future cancer epidemic, write Mark Lawler and Mirjam Crul. Data driven approaches offer the best way forward